Massive Hemoptysis and Pulmonary Thromboembolism in a Patient with Pulmonary Tuberculosis: A Therapeutic Conundrum Managed with Bronchial Artery Embolization - Vaidya, N.; Karmacharya, R. M.; Vaidya, S.; Bade, S.; Bade, S.; Paudel, K.; Kandel, G.; Thapa, P.; Maharjan, R.; Duwal, S.; Karki, Y. (Kathmandu University Medical Journal, 2022)
Hemoptysis is a crucial entity taking into account its morbidity and mortality. Pulmonary tuberculosis is the leading cause for massive hemoptysis in our part of the world, which if left untreated may be life threatening. We present a case of a 37-year-old male patient with pulmonary tuberculosis with concurrent pulmonary thromboembolism presenting with massive hemoptysis, which was successfully managed with Bronchial Artery Embolization. This case represents that this measure can be a viable therapeutic choice for a patient with a severe life-threatening hemoptysis, particularly when other treatment options are unavailable or ineffective.